Incorporation of antimicrobial agents into dental materials obtained by additive manufacturing: A literature review - Ana Beatriz Vilela Teixeira; Gabriela Greghi de Carvalho; Andréa Cândido dos Reis (Elsevier, 2022)
Background: This review aimed to identify antimicrobial agents incorporated into dental materials obtained through additive manufacturing and their efficacy. Methods: Protocol registration was performed in Open Science Framework (osf.io/sp3xa/) and an electronic search was carried out in the databases PubMed, Science Direct, Embase, Lilacs, and Scopus, up to February 2022, combining the terms ("additive manufacturing" OR "3D printing") AND (antimicrobial). Eligibility criteria included: experimental studies that incorporated 3D printing material with an antimicrobial agent for dental application; that evaluated antimicrobial activity; articles published in peer-reviewed journals and in English. Results: The database search resulted in 1139 references. The manual selection was carried out in 851 studies. Twenty-five articles were selected for full-text reading, of which 8 were included in this review. Polymers were the dental materials most often modified with antimicrobial agents for 3D printing, followed by metal alloy. The antimicrobials used were mainly nanoparticles, metal particles, antifungals, monomers containing quaternary ammonium salt, and antiseptics such as chlorhexidine. Conclusion: The addition of the antimicrobial agents in polymers and alloy for additive manufacturing showed promising efficacy against Candida spp., Gram-positive and Gram-negative bacteria.